POLICY ANALYSIS OF SEAWEED FARMING DEVELOPMENT (Eucheuma cottonii) IN WAKATOBI: ANALISIS KEBIJAKAN PENGEMBANGAN BUDIDAYA RUMPUT LAUT (Eucheuma cottonii) di WAKATOBI - Sutaman Sutaman; Alin Fithor; Heru Kurniawan Alamsyah; Kusnandar Kusnandar (Jurnal Teknologi Perikanan dan Kelautan, 2026)
Seaweed is an important commodity with high economic value and significant benefits for human life. Besides being a food ingredient, seaweed is also a raw material for the pharmaceutical, cosmetics, and other industries, thereby increasing demand for it both domestically and for export. In 2021, Indonesia's export volume was 225,000 tons, while China's, Indonesia's main competitor, was 148,306.9 tons. Indonesia is the second-largest seaweed exporter after China, with HS codes 121221 (for human consumption) and 121229 (for industrial use). The purpose of this study was to analyze the policy for the development of seaweed (Eucheuma cottonii) farming in the Wakatobi conservation area. Data used in this study were collected through structured interviews, direct observations of seaweed farming activities and the surrounding environment, and the farming community. The method used in this study was a SWOT analysis. The results of this study explain that seaweed farming in Wakatobi is profitable but still requires significant support from various parties.